Coproduction of liquid transportation fuels and C6_C8 aromatics from biomass and natural gas. Issue 3 (6th February 2015) - Niziolek, Alexander M.; Onel, Onur; Elia, Josephine A.; Baliban, Richard C.; Floudas, Christodoulos A.
<x xml:space="preserve">Abstract</x> The coproduction of liquid transportation fuels and C6C8 aromatics from the thermochemical conversion of biomass and natural gas (BGTL+C6_C8) is investigated in this article. An optimization‐based process synthesis framework incorporating multiple synthesis gas conversion technologies, such as Fischer–Tropsch synthesis or methanol conversion, is described. Production of aromatics can proceed through several technologies, such as naphtha reforming and aromatization of hydrocarbons via a metal‐promoted H‐ZSM‐5 catalyst. This is the first article in the literature to incorporate an aromatics complex for the coproduction of liquid fuels and C6C8 petrochemicals within a rigorous process synthesis and deterministic global optimization framework. The optimal process topologies across several case studies are discussed and the results indicate that the coproduction of aromatics with liquid fuels can significantly increase the profitability of these refineries. © 2015 American Institute of Chemical Engineers AIChE J, 2015 2014 American Institute of Chemical Engineers AIChE J, 61: 831–856, 2015